Financial systems and venture capital in Nordic countries: A comparative study - Ari Hyytinen; Mika Pajarinen (The Research Institute of the Finnish Economy (ETLA), 2001)
In this paper we present a comparative analysis of Nordic countries' financial systems and consider in particular the recent growth of Nordic venture capital industries. We document that the Nordic countries' financial systems display several similarities that have characterized their evolution over the past decades. These include the liberalization of financial markets in the 1980s, the banking crises in the early 1990s and the renaissance of stock markets in the second half of the 1990s. It seems that during the past decade the Nordic countries' financial systems have not necessarily grown larger overall. However, the financial systems have become more stock market-centered. This characterization seems to apply particularly to Finland. We also show that the Nordic private equity industries have evolved in tandem with the overall macroeconomic conditions and stock market developments. Despite the growth in recent years, only the Swedish venture capital market has reached the scale of fundraising and investment activity that the country's GDP share in Europe predicts. For the scale of activity achieved, the Nordic countries are also laggards compared to the stage of the average European private equity cycle. Only in Norway, the amount of funds raised, investments and exits are balanced relative to each other when benchmarked to the corresponding European levels; the other Nordic countries' private equity industries are at an earlier stage of the cycle. This suggests that the Nordic venture capital may lack a degree or two of maturity when compared to the other European countries, and emphasizes particularly the importance of successful exits. We also discuss the implications and challenges that the documented recent changes in the financial systems imply for the Nordic countries. – – Tässä tutkimuksessa tarkastellaan ja vertaillaan rahoitusjärjestelmien kehitystä ja erityisesti pääomasijoitustoimialan kasvua Pohjoismaissa. Rahoitusjärjestelmien kehitys on Pohjoismaissa ollut viime vuosikymmenten aikana monella tavoin samankaltaista: rahoitusmarkkinat vapautettiin 1980-luvulla, 1990-luvun alkupuolella koettiin pankkikriisi ja 1990-luvun jälkipuoliskolla osakemarkkinat kukoistivat. Rahoitusmarkkinoiden koko suhteessa kansantalouksien kokoon ei ole selkeästi kasvanut viime vuosikymmenen aikana, mutta toisaalta rahoitusjärjestelmistä on tullut selvästi aikaisempaa markkinaehtoisempia ja osakemarkkinakeskeisempiä. Erityisesti Suomessa tämä kehitys on ollut selvästi nähtävissä. Pääomasijoitustoiminnan kehitys on puolestaan seurannut makrotalouden ja osakemarkkinoiden kehitystä. Huolimatta voimakkaasta kasvusta viime vuosina, vain Ruotsissa pääomasijoitustoimialasta on tullut niin suuri, että se vastaa maan BKT-osuutta Euroopassa. Toisaalta pohjoismaiset pääomasijoittajat ovat – ehkä Norjaa lukuunottamatta – edelleen pääomasijoitussyklissä jäljessä muita eurooppalaisia maita. Heillä on siten vähemmän kokemusta sijoitus- ja irtautumistoiminnasta kuin eurooppalaisilla toimijoilla keskimäärin ja suurempi tarve mm. onnistuneisiin irtautumisiin kohdeyrityksistä tulevaisuudessa. – pääomasijoittaminen ; yritysrahoitus ; rahoituksen välitys
Keywords: 330; venture capital; corporate finance; financial intermediation; Risikokapital; Unternehmensfinanzierung; Vergleich; Finnland; Dänemark; Schweden; Norwegen